ChemInform Abstract: Earth‐Abundant Hydrogen Evolution Electrocatalysts. Issue 15 (15th April 2014) - McKone, James R.; Marinescu, Smaranda C.; Brunschwig, Bruce S.; Winkler, Jay R.; Gray, Harry B.
Abstract Review: 155 refs.